Reducing Alcohol - Your Breast Bet - Christensen, Kelly; Silvester, Morgan; Sutaroski, Melissa (Université d'Ottawa | University of Ottawa, 2015)
Background: Last year an estimated 14 women died every day from breast cancer (1). A common misconception among women is that the diagnosis is beyond their control; therefore, more research and dissemination is required to contest this misbelief and encourage women to play a more active role in their health (2). Objective: To summarize relevant literature and critically assess the evidence indicating an association between moderate alcohol consumption and breast cancer risk. Methods: A systematic review was conducted using the Scholars Portal database and findings were restricted to published articles from 1995-2015. The search was performed using the keywords “alcohol consumption” AND “breast cancer risk” and a total of 8 articles were selected based on specific inclusion and exclusion criteria. Results: Upon review of the articles, 7 found a definitive link between moderate alcohol consumption and increased risk of breast cancer. The general consensus of moderate alcohol consumption equated to 20-30g/day, which is roughly 1.5-2 alcoholic drinks. One study found that alcohol consumption as low as 5g/day (½ of an alcoholic drink) increased breast cancer risk. Conclusion: The findings indicated there was a statistically significant relationship between moderate alcohol consumption and increased risk for breast cancer. Discordance, however, does exist among which characteristics of alcohol consumption play the biggest role in increasing risk, with some noting average quantity, intensity, or timing and age as the most important risk factor; therefore, warranting further investigation.